Effect of the Alterations in Contractility and Morphology Produced by Atrial Fibrillation on the Thrombosis Potential of the Left Atrial Appendage - Vella, Danila; Monteleone, Alessandra; Musotto, Giulio; Bosi, Giorgia Maria; Burriesci, Gaetano (Frontiers in Bioengineering and Biotechnology, 2021)
Atrial fibrillation (AF) is a common arrhythmia mainly affecting the elderly population, which can lead to serious complications such as stroke, ischaemic attack and vascular dementia. These problems are caused by thrombi which mostly originate in the left atrial appendage (LAA), a small muscular sac protruding from left atrium. The abnormal heart rhythm associated with AF results in alterations in the heart muscle contractions and in some re-shaping of the cardiac chambers. This study aims to verify if and how these physiological changes can establish haemodynamic conditions in the LAA promoting thrombus formation, by means of computational fluid dynamic (CFD)analyses. In particular, sinus and fibrillation contractility was replicated by applying wall velocity/motion to models based on healthy and dilated idealised shapes of the left atrium with a common LAA morphology. The models were analysed and compared in terms of shear strain rate (SSR)and vorticity, which are haemodynamic parameters directly associated with thrombogenicity. The study clearly indicates that the alterations in contractility and morphology associated with AF pathologies play a primary role in establishing haemodynamic conditions which promote higher incidence of ischaemic events, consistently with the clinical evidence. In particular, in the analysed models, the impairment in contractility determined a decrease in SSR of about 50%, whilst the chamber pathological dilatation contributed to a 30% reduction, indicating increased risk of clot formation. The equivalent rigid wall model was characterised by SSR values about one order of magnitude smaller than in the contractile models, and substantially different vortical behaviour, suggesting that analyses based on rigid chambers, although common in the literature, are inadequate to provide realistic results on the LAA haemodynamics.